Pembatasan Hak Politik Mantan Terpidana Mengikuti Kontestasi Pemilihan Umum 2024 di Indonesia (SETARA : Jurnal Ilmu Hukum, 2023)
This article examines the limitation of political rights for former convicts in the 2024 Indonesian general election, particularly in relation to candidacy for the Regional Representative Council. The issue arises because Constitutional Court decisions have imposed a five-year waiting period for former convicts seeking certain elected offices, yet the same restriction has not been applied consistently to candidates for the Regional Representative Council. Using normative juridical research, the article reviews Constitutional Court decisions, Law Number 7 of 2017 on General Elections, and the constitutional structure of representative institutions. The study finds that the current regulatory arrangement creates unequal treatment among political offices that are equally filled through electoral mechanisms. As a result, the open legal policy of the legislature appears inconsistent and risks undermining the constitutional objective of clean, honest, and integrity-based public leadership. The article concludes that legal harmonization is needed so that limitations on the political rights of former convicts are formulated consistently across elective offices, including candidacy for the Regional Representative Council.
Keywords: Former Convicts; Political Rights; General Election 2024; Regional Representative Council; Constitutional Court